2021
DOI: 10.3390/biology10020110
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of Cystatins of Early-Emerging Metazoans Reveals a Novel Subtype in Parasitic Cnidarians

Abstract: The evolutionary aspects of cystatins are greatly underexplored in early-emerging metazoans. Thus, we surveyed the gene organization, protein architecture, and phylogeny of cystatin homologues mined from 110 genomes and the transcriptomes of 58 basal metazoan species, encompassing free-living and parasite taxa of Porifera, Placozoa, Cnidaria (including Myxozoa), and Ctenophora. We found that the cystatin gene repertoire significantly differs among phyla, with stefins present in most of the investigated lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…The four protease protein sequences were used as queries to find homologous genes in seven myxozoan transcriptomes: Tetracapsuloides bryosalmonae, Sphaerospora molnari, Myxobolus cerebralis, Myxobolus squamalis, Henneguya salminicola and Kudoa iwatai to compare their protease repertoire with that of our model organism transcriptome, C. shasta (genotype IIR). Similar searches were done for myxozoan stefins in a previous publication (Bartosǒva-Sojkováet al, 2021) and are discussed herein. Transcriptomes were downloaded from public data repositories (figshare, Dryad and Transcriptome Shotgun Assembly Sequence Database or TSA at NCBI, see Table 2).…”
Section: Protease Gene Mining In Myxozoans Transcriptomesmentioning
confidence: 90%
See 2 more Smart Citations
“…The four protease protein sequences were used as queries to find homologous genes in seven myxozoan transcriptomes: Tetracapsuloides bryosalmonae, Sphaerospora molnari, Myxobolus cerebralis, Myxobolus squamalis, Henneguya salminicola and Kudoa iwatai to compare their protease repertoire with that of our model organism transcriptome, C. shasta (genotype IIR). Similar searches were done for myxozoan stefins in a previous publication (Bartosǒva-Sojkováet al, 2021) and are discussed herein. Transcriptomes were downloaded from public data repositories (figshare, Dryad and Transcriptome Shotgun Assembly Sequence Database or TSA at NCBI, see Table 2).…”
Section: Protease Gene Mining In Myxozoans Transcriptomesmentioning
confidence: 90%
“…Stefins are tight binding intracellular inhibitors of the papain family of cysteine proteases that generally lack a signal peptide, and hence are usually involved in regulation of endopeptidases (Turk et al, 2008). Myxozoan stefins are atypical molecules with a chimeric structure combining motifs of type 1 cystatin or classical stefins and type 2 cystatins (Bartosǒva-Sojkováet al, 2021). While some myxozoan stefins posses a signal peptide, C. shasta stefin lacks this feature, which suggests it has intracellular/ cytoplasmic localization.…”
Section: The Virulent Genotype Requires Endogenous Cysteine Protease Regulation By Its Stefinmentioning
confidence: 99%
See 1 more Smart Citation
“…In genotype IIR, the stefin was present in proteomic data from ascites but absent from myxospores (Brekhman et al ., 2021), indicating some cell regulatory function in developmental stages. A contrasting expression profile between genotypes and the cathepsin D and the stefin 3D protein structures suggests these molecules are key for the rapid proliferation and metabolism of genotype IIR (Bartošová-Sojková et al ., 2021; Alama-Bermejo et al ., 2022).…”
Section: Parasite Factors Driving Diseasementioning
confidence: 99%
“…The team set out hypotheses to describe the driving forces for the origins of this unique cystatin subtype and propose evolutionary scenarios elucidating the current existence of cystatins in the Metazoa, especially in their early emerging lineages. Their study identified molecules for which future functional studies could help to identify their roles in parasites and host–parasite interactions [ 5 ].…”
mentioning
confidence: 99%